Detection of microvascular retinal changes in type I diabetic mice with optical coherence tomography angiography. (January 2019) - Uehara, Hironori; Lesuma, Timilai; Stocking, Parker; Jensen, Nathan; Kumar, Sangeetha Ravi; Zhang, Mingyang Aaron; Choi, Susie; Zhang, Xiaohui; Archer, Bonnie; Carroll, Lara; Ambati, Balamurali K.
Abstract: Optical coherence tomography (OCT) angiography is a dye-free and non-invasive angiography which allows visualization of retinal and choroid vascular flow, enabling observation of highly permeable and three dimensional vasculature. Although OCT angiography is providing new insights in human retinal and choroidal diseases, a few studies have been reported in experimental mice. In this study, to determine the potential of OCT angiography in experimental mice, we sought to examine whether OCT angiography can detect vascular change in type I diabetic mice. To conduct age dependent analysis, 2 and 6 month old male type 1 diabetic Ins2 Akita/+ and age matched C57BL/6J mice were used. OCT angiography was performed by Heidelberg Spectralis OCT Angiography Module with 30° lens + mouse adapter lens. We acquired the OCT angiography image from the peripheral nasal position. For analysis of OCT angiography images, OCT angiography positive area were used for vascular density. We analyzed vascular density from the retinal surface (inner limiting membrane) to 120 μm depth with 4 μm steps in order to correlate vascular density vs depth (N = 4 per group). Vascular density of both mouse strains demonstrated three different peaks. By comparing with the OCT image, the first peak (superficial), second peak (intermediate) and third peak (deep) were located in nerve fiber layer/ganglion cell layer, inner plexiform layer/inner nuclear layer and outer plexiform layer/outer nuclear layer, respectively. We calculated vascular density of these peaks separately. In C57BL/6J mice, the vascular density in all three layers do not show significant difference between 2- and 6-month-old. On the other hand, 6-month-old Ins2 Akita/+ mice showed a significant decrease of the vascular density in all three layers compared to 2-month-old Ins2 Akita/+ mice. Also, the vascular density of 6-month-old Ins2 Akita/+ mice in the deep layer showed a significant decrease compared to 2- and 6-month-old C57BL/6J mice. Thus, OCT angiography successfully detects retinal vascular difference between type I diabetic mice and control mice, and age-dependent vasculature change in type I diabetic mice. The diabetic mice demonstrated reduced vascular density due to reduced density of flowing deep vessels. Importantly, we observed this difference without retinal blood leakage, hemorrhage or neovascularization. Our analysis (vascular density vs retinal depth) suggests that OCT angiography is useful for in vivo detection of retinal vasculature alteration in experimental mice. Highlights: OCT angiography enables three dimensional retinal vasculature analysis in mice. Aged diabetic mice show diminished deep retinal vascular layer. Aged diabetic mice demonstrate a similar phenotype to human diabetic retinopathy.